Comparing Advanced Constitutive Models in Stability Analysis of Slopes on Liquefiable Layers under Seismic Loading Conditions - M. R. Motahari; F. Sadat Alhosseini (Numerical Methods in Civil Engineering)
One of the most challenging issues in the field of geotechnical engineering is liquefaction that causes great damage to the earth slopes during earthquakes. Since seismic analysis and modeling of liquefaction phenomenon in loose saturated sandy soils requires the use of advanced constitutive models, two different approaches are used for analyzing the response of slopes on liquefiable layers, including (1) UBCSAND (UBC) and (2) Mohr Coulomb (MC) and Finn constitutive models. In the current paper, to assess the liquefaction potential, firstly a comparison will be done among different constitutive models, then seismic stability analysis of slopes on liquefiable layers are studied by finite difference method using FLAC2D. The results of dynamic analysis indicated that, estimated seismic displacements using advanced constitutive models are more accurate than the ones using common models. Subsequently, the effects of different parameters such as the thickness of liquefiable layer and the frequency content have been investigated. Finally, the relationship among mentioned parameters and horizontal displacement of the slopes is investigated using the MC, Finn and UBC constitutive models. It should be mentioned that, the reduction in frequency and increase in the thickness of liquefiable layer have an increasing effect on the horizontal displacement of slopes.